Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

What tricks are there for calculating the roots of complex polynomials like

$$p(t) = (t+1)^6 - (t-1)^6$$


$t = 1$ is not a root. Therefore we can divide by $(t-1)^6$. We then get

$$\left( \frac{t+1}{t-1} \right)^6 = 1$$

Let $\omega = \frac{t+1}{t-1}$ then we get $\omega^6=1$ which brings us to

$$\omega_k = e^{i \cdot k \cdot \frac{2 \pi}{6}}$$

So now we need to get the values from t for $k = 0,...5$.

How to get the values of t from the following identity then?

$$ \begin{align} \frac{t+1}{t-1} &= e^{i \cdot 2 \cdot \frac{2 \pi}{6}} \\ (t+1) &= t\cdot e^{i \cdot 2 \cdot \frac{2 \pi}{6}} - e^{i \cdot 2 \cdot \frac{2 \pi}{6}} \\ 1+e^{i \cdot 2 \cdot \frac{2 \pi}{6}} &= t\cdot e^{i \cdot 2 \cdot \frac{2 \pi}{6}} - t \\ 1+e^{i \cdot 2 \cdot \frac{2 \pi}{6}} &= t \cdot (e^{i \cdot 2 \cdot \frac{2 \pi}{6}}-1) \\ \end{align} $$

And now?

$$ t = \frac{1+e^{i \cdot 2 \cdot \frac{2 \pi}{6}}}{e^{i \cdot 2 \cdot \frac{2 \pi}{6}}-1} $$

So I've got six roots for $k = 0,...5$ as follows

$$ t = \frac{1+e^{i \cdot k \cdot \frac{2 \pi}{6}}}{e^{i \cdot k \cdot \frac{2 \pi}{6}}-1} $$

Is this right? But how can it be that the bottom equals $0$ for $k=0$?

I don't exactly know how to simplify this:

$$\frac{ \frac{1}{ e^{i \cdot k \cdot \frac{2 \pi}{6}} } + 1 }{ 1 - \frac{1}{ e^{i \cdot k \cdot \frac{2 \pi}{6}} }}$$

share|improve this question
    
Yes, it is right. And divide top and bottom by $e^{\pi i k/6}$. On top you get $2\cos(k\pi/6)$. On the bottom you get $2i\sin(k\pi/6)$. The answers simplify to $-i\cot(k\pi/6)$. –  André Nicolas Feb 2 '12 at 23:57

2 Answers 2

up vote 3 down vote accepted

Notice that $t=1$ is not a root. Divide by $(t-1)^6$.

If $\omega$ is a root of $z^6 - 1$, then a root of the original equation is given by $\frac{t+1}{t-1} = \omega$.

share|improve this answer
    
So I've got the roots of $z^6 -1$ as $\omega_k = e^{i\cdot k\cdot\frac{2\pi}{6}}$. How to conclude now $t$ for example from $\frac{t+1}{t-1}=\omega_1$? –  meinzlein Feb 2 '12 at 23:24
    
Try multiplying by $t-1$... –  Aryabhata Feb 2 '12 at 23:32
    
I tried and edited the original post accordingly.. –  meinzlein Feb 2 '12 at 23:42
    
Looks right.... –  Aryabhata Feb 2 '12 at 23:54
    
Well a collegue of mine tried the way mentioned by André Nicolas and got only five roots: $$t_{1}=0$$ $$t_{2,3} = \pm \sqrt{3} i, $$ $$t_{4,5} = \pm \sqrt{\frac{1}{3}} i$$But I got 6 roots (see original post).. Where's the problem? –  meinzlein Feb 2 '12 at 23:58

Note that $$(t+1)^6 - (t-1)^6=((t+1)^3-(t-1)^3)((t+1)^3+(t-1)^3)$$ (difference of squares).

When you simplify the first term in the product on the right, there is no $t^3$ term and no $t$ term! The second term in the product simplifies to $2t^3+6t$.

Remark: The solution by Arhabhata is the right one, it works if we replace $6$ by $n$. And when we set $\frac{t-1}{t+1}=e^{2\pi i k/n}$, where $k=1,2,\dots,n-1$, and solve for $t$, we get $-i$ times cotangents.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.